A Mechanism of Gene Amplification Driven by Small DNA Fragments - Mukherjee, Kuntal (Public Library of Science, 2012)
DNA amplification is a molecular process that increases the copy number of a chromosomal tract and often causes elevated expression of the amplified gene(s). Although gene amplification is frequently observed in cancer and other degenerative disorders, the molecular mechanisms involved in the process of DNA copy number increase remain largely unknown. We hypothesized that small DNA fragments could be the trigger of DNA amplification events. Following our findings that small fragments of DNA in the form of DNA oligonucleotides can be highly recombinogenic, we have developed a system in the yeast Saccharomyces cerevisiae to capture events of chromosomal DNA amplification initiated by small DNA fragments. Here we demonstrate that small DNAs can amplify a chromosomal region, generating either tandem duplications or acentric extrachromosomal DNA circles. Small fragment-driven DNA amplification (SFDA) occurs with a frequency that increases with the length of homology between the small DNAs and the target chromosomal regions. SFDA events are triggered even by small single-stranded molecules with as little as 20-nt homology with the genomic target. A double-strand break (DSB) external to the chromosomal amplicon region stimulates the amplification event up to a factor of 20 and favors formation of extrachromosomal circles. SFDA is dependent on Rad52 and Rad59, partially dependent on Rad1, Rad10, and Pol32, and independent of Rad51, suggesting a single-strand annealing mechanism. Our results reveal a novel molecular model for gene amplification, in which small DNA fragments drive DNA amplification and define the boundaries of the amplicon region. As DNA fragments are frequently found both inside cells and in the extracellular environment, such as the serum of patients with cancer or other degenerative disorders, we propose that SFDA may be a common mechanism for DNA amplification in cancer cells, as well as a more general cause of DNA copy number variation in nature.